A Johnny Amidst Jugnus. Issue 1 (March 2021) - Zahid, Adnan; Zaffar, M. Adeel; Aurengzeb, Hamza
The case recounts the story of Johnny and Jugnu, the fast-food restaurant's initial journey. The story is then supplemented by details of the marketing mix (price, product, place and promotion). All decisions have been made, except for the pricing decision. The case hinges on this important decision. The four partners seem to disagree on pricing, and the case data helps students make this decision for the protagonists.